Numerical and experimental analysis of forced convection in rib‐roughened channels with moisture‐permeable walls. Issue 2 (4th October 2019) - Sylvester, Alexander; Engarnevis, Amin; Kadylak, David; Huizing, Ryan; Rogak, Steven; Green, Sheldon
Abstract: Ribbed features can promote mixing and improve convective heat and mass transfer in channels. This can be beneficial in certain exchangers, such as Energy Recovery Ventilators (ERVs), which employ moisture‐permeable membranes to transfer both latent and sensible heat. In this work, a computational fluid dynamics model with experimental validation was used to study angled rib mixing features in compact channels. Results show that, relative to a smooth channel, the ribs increase the channel Sherwood and Nusselt numbers by a larger fraction than the corresponding increase in friction factor. For a typical commercial grade ERV, total effectiveness can be improved by over 10% for an equal pressure drop by adding ribs and slightly increasing the channel height. A custom test stand and rib‐forming technique were developed to validate the simulation predictions. The experiments confirm the net benefit of ribbed channels and agree with the simulation results within experimental uncertainty.